Accumulation of trace metals in freshwater macroinvertebrates across metal contamination gradients. (1st May 2021) - Arnold, Amanda; Murphy, John F.; Pretty, James L.; Duerdoth, Charles P.; Smith, Brian D.; Rainbow, Philip S.; Spencer, Kate L.; Collins, Adrian L.; Jones, J. Iwan
Abstract: Historical mining activities cause widespread, long-term trace metal contamination of freshwater ecosystems. However, measuring trace metal bioavailability has proven difficult, because it depends on many factors, not least concentrations in water, sediment and habitat. Simple tools are needed to assess bioavailabilities. The use of biomonitors has been widely advocated to provide a realistic measure. To date there have been few attempts to identify ubiquitous patterns of trace metal accumulation within and between freshwater biomonitors at geographical scales relevant to trace metal contamination. Here we address this through a nationwide collection of freshwater biomonitors (species of Gammarus, Leuctra, Baetis, Rhyacophila, Hydropsyche ) from 99 English and Welsh stream sites spanning a gradient of high to low trace metal loading. The study tested for inter-biomonitor variation in trace metal body burden, and for congruence amongst accumulations of trace metals within taxa and between taxa across the gradient. In general, significant differences in trace metal body burden occurred between taxa: Gammarus sp. was the most different compared with insect biomonitors. Bivariate relationships between trace metals within biomonitors reflected trace metal profiles in the environment. Strong correlations between some trace metals suggested accumulation was also influenced by physiological pathways. Bivariate relationships between insect biomonitors for body burdens of As, Cu, Mn and Pb were highly consistent. Our data show that irrespective of taxonomic or ecological differences, there is a commonality of response amongst insect taxa, indicating one or more could provide consistent measures of trace metal bioavailability. Graphical abstract: Image 1 Highlights: Quantification of trace metals in biomonitors across contaminant gradients. Trace metal body burden differs between biomonitors especially Gammarus . Many associations between trace metals within biomonitors were due to geology. Accumulations of As, Cu, Mn and Pb were consistent between insect biomonitors. Insect biomonitors had a consistent response to trace metal contamination gradients. Abstract : Aquatic insect biomonitors had corresponding patterns of trace metal accumulation across contamination gradients.